Individualized, Intraoperative Dosing of Fibrinogen Concentrate for the Prevention of Bleeding in Neonatal and Infant Cardiac Surgery Using Cardiopulmonary Bypass (FIBCON): A Phase 1b/2a Randomized Controlled Trial. (December 2020) - Siemens, Kristina; Hunt, Beverley J.; Harris, Julia; Nyman, Andrew G.; Parmar, Kiran; Tibby, Shane M.
Abstract : Background: Mediastinal bleeding is common following pediatric cardiopulmonary bypass surgery for congenital heart disease. Fibrinogen concentrate (FC) represents a potential therapy for preventing bleeding. Methods: We performed a single-center, phase 1b/2a, randomized controlled trial on infants 2.5 to 12 kg undergoing cardiopulmonary bypass surgery, aimed at (1) demonstrating the feasibility of an intraoperative point-of-care test, rotational thromboelastometry, to screen out patients at low risk of postoperative bleeding and then guide individualized FC dosing in high-risk patients and (2) determining the dose, safety, and efficacy of intraoperative FC supplementation. Screening occurred intraoperatively 1-hour before bypass separation using the rotational thromboelastometry variable fibrinogen thromboelastometry maximum clot firmness (FibTEM-MCF; fibrinogen contribution to clot firmness). If FibTEM-MCF ≥7 mm, patients entered the monitoring cohort. If FibTEM-MCF ⩽6 mm, patients were randomized to receive FC/placebo (2:1 ratio). Individualized FC dose calculation included weight, bypass circuit volume, hematocrit, and intraoperative measured and desired FibTEM-MCF. The coprimary outcomes, measured 5 minutes post-FC administration were FibTEM-MCF (desired range, 8–13 mm) and fibrinogen levels (desired range, 1.5–2.5 g/L). Secondary outcomes were thrombosis and thrombosis-related major complications and postoperative 24-hour mediastinal blood loss. Results: We enrolled 111 patients (cohort, n=21; FC, n=60; placebo, n=30); mean (SD) age, 6.4 months (5.8); weight, 5.9 kg (2.0). Intraoperative rotational thromboelastometry screening effectively excluded low-risk patients, in that none in the cohort arm (FibTEM-MCF, ≥7 mm) demonstrated clinically significant early postoperative bleeding (>10 mL/kg per 4 hours). Among randomized patients, the median (range) FC administered dose was 114 mg/kg (51–218). Fibrinogen levels increased from a mean (SD) of 0.91 (0.22) to 1.7 g/L (0.41). The postdose fibrinogen range was 1.2 to 3.3 g/L (72% within the desired range). The corresponding FibTEM-MCF values were as follows: pre-dose, 5.3 mm (1.9); post-dose, 13 mm (3.2). Ten patients (8 FC and 2 placebo) exhibited 12 possible thromboses; none were clearly related to FC. There was an overall difference in mean (SD) 24-hour mediastinal drain loss: cohort, 12.6 mL/kg (6.4); FC, 11.6 mL/kg (5.2); placebo, 17.1 mL/kg (14.3; ANOVA P =0.02). Conclusions: Intraoperative, individualized dosing of FC appears feasible. The need for individualized dosing is supported by the finding that a 4-fold variation in FC dose is required to achieve therapeutic fibrinogen levels. Registration: URL: https://eudract.ema.europa.eu/ ; Unique identifier: 2013-003532-68. URL: https://www.isrctn.com/ ; Unique identifier: 50553029. Abstract : Supplemental Digital Content is available in the text.